Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/app.41204
|View full text |Cite
|
Sign up to set email alerts
|

Modification of chitosan onto PE by irradiation in salt solutions and possible use as Cu2+ complex film for pest snail control

Abstract: Chitosan‐grafted‐polyethylene (CS‐g‐PE) film was prepared using simultaneous radiation‐inducing grafting technique. The copper ion (Cu2+) adsorptivity on the CS‐g‐PE film was determined. The CS‐hydroxybenzyltriazole (CS‐HOBt), CS‐N‐hydroxysuccinimide (CS‐NHS), CS‐acetic acid (CS‐HOAc), and CS‐glutathione (CS‐GSH) were used as CS‐salts in aqueous solutions. Among these grafting solution systems, the CS‐g‐PE film prepared from CS‐HOBt solution showed the greatest grafting amount and highest Cu2+ adsorptivity, up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Moreover, the increase in the water angle indicates the decrease in the hydrophilic character and wettability of the surface of the CS-modified film. The presence of −OH and −NH 2 groups in CS is responsible for the hydrophilic character and wettability of the CS polymer, so the decrease of this parameter corroborates the previous assignment of physical and intermolecular interactions, mainly hydrogen bonds, between [Fe­(CN) 5 (NH 3 )] 3– and CS via −NH 2 and −OH fragments …”
Section: Resultssupporting
confidence: 88%
“…Moreover, the increase in the water angle indicates the decrease in the hydrophilic character and wettability of the surface of the CS-modified film. The presence of −OH and −NH 2 groups in CS is responsible for the hydrophilic character and wettability of the CS polymer, so the decrease of this parameter corroborates the previous assignment of physical and intermolecular interactions, mainly hydrogen bonds, between [Fe­(CN) 5 (NH 3 )] 3– and CS via −NH 2 and −OH fragments …”
Section: Resultssupporting
confidence: 88%
“…The XRD pattern of DC-WCS showed a significant broad diffraction peak at 19.7° (2θ) because of changes in the morphology of WCS resulting from insertion of the DC moieties ( Figure 1 (Cb)). The DC conjugate brought about a more amorphous structure of CS because the hydrophobic bulky structure of DC obstructed the inter- and intra-molecular hydrogel bonding of CS [ 25 , 27 ]. New hydrogen bonds could also occur between the –OH group of DC and the functional groups of WCS (i.e., –NH 2 , –OH, C–O–C, and C=O).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the characteristic crystalline peak of PEGMA was found at 14.5° and 30.4° (2θ) when PEGMA was grafted onto CS [ 27 ]. As in the previous work, DC-CS-PG was used for comparative study, and diffraction peaks were observed at 12.8°, 18.7°, 21.6°, and 23.9° (2θ) [ 25 , 38 ]. For CS modified with PEG, two strong crystalline peaks at 19.3–23.6° (2θ) and two broad crystalline peaks around 26−31° (2θ) were assigned to the PEG crystalline [ 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation